Factors influencing estimates of coordinate error for molecular replacement. Issue 1 (2nd January 2020) - Hatti, Kaushik S.; McCoy, Airlie J.; Oeffner, Robert D.; Sammito, Massimo D.; Read, Randy J.
Abstract : Improved coordinate error estimates are proposed for the X‐ray and NMR models used for maximum‐likelihood‐based molecular‐replacement phasing. Abstract : Good prior estimates of the effective root‐mean‐square deviation (r.m.s.d.) between the atomic coordinates of the model and the target optimize the signal in molecular replacement, thereby increasing the success rate in difficult cases. Previous studies using protein structures solved by X‐ray crystallography as models showed that optimal error estimates (refined after structure solution) were correlated with the sequence identity between the model and target, and with the number of residues in the model. Here, this work has been extended to find additional correlations between parameters of the model and the target and hence improved prior estimates of the coordinate error. Using a graph database, a curated set of 6030 molecular‐replacement calculations using models that had been solved by X‐ray crystallography was analysed to consider about 120 model and target parameters. Improved estimates were achieved by replacing the sequence identity with the Gonnet score for sequence similarity, as well as by considering the resolution of the target structure and the MolProbity score of the model. This approach was extended by analysing 12 610 additional molecular‐replacement calculations where the model was determined by NMR. The median r.m.s.d. between pairs of models in an ensemble was found to be correlated with the estimated r.m.s.d. to the target. For models solved by NMR, the overall coordinate error estimates were larger than for structures determined by X‐ray crystallography, and were more highly correlated with the number of residues.